2022
DOI: 10.3390/md20010053
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Drug Design (CADD) to De-Orphanize Marine Molecules: Finding Potential Therapeutic Agents for Neurodegenerative and Cardiovascular Diseases

Abstract: Computer-aided drug design (CADD) techniques allow the identification of compounds capable of modulating protein functions in pathogenesis-related pathways, which is a promising line on drug discovery. Marine natural products (MNPs) are considered a rich source of bioactive compounds, as the oceans are home to much of the planet’s biodiversity. Biodiversity is directly related to chemodiversity, which can inspire new drug discoveries. Therefore, natural products (NPs) in general, and MNPs in particular, have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 173 publications
(243 reference statements)
0
3
0
Order By: Relevance
“…Meridianins have been isolated from different specimens of the tunicate genera Aplidium and Synoicum [ 36 , 37 ]; however, it is still unclear whether tunicates are the true producers of the molecules or whether the associated microbes may play a role in their synthesis and chemical ecology [ 28 , 39 ]. The potential of meridianins as bioactive drugs has been reported previously [ 33 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Recently, we showed that meridianins can act as the ATP-competitive or non-ATP-competitive inhibitors of GSK3β in vitro without altering neuronal survival [ 54 ].…”
Section: Introductionmentioning
confidence: 85%
“…Meridianins have been isolated from different specimens of the tunicate genera Aplidium and Synoicum [ 36 , 37 ]; however, it is still unclear whether tunicates are the true producers of the molecules or whether the associated microbes may play a role in their synthesis and chemical ecology [ 28 , 39 ]. The potential of meridianins as bioactive drugs has been reported previously [ 33 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Recently, we showed that meridianins can act as the ATP-competitive or non-ATP-competitive inhibitors of GSK3β in vitro without altering neuronal survival [ 54 ].…”
Section: Introductionmentioning
confidence: 85%
“…The role of CADD in cardiovascular diseases : Cardiovascular diseases (CVD) are considered the first cause of death globally 178 . It is common to have significant coronary heart disease, myocardial ischemia and hypertension, as well as diabetes-related complications 179 .…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the advancements made in informatics and computational biology, as well as parallel increases in drug development productivity, drug development has been sluggish due to heavy dependence on synthetic small molecules as a source of innovation. Computer-Aided Drug Design (CADD) has emerged as a highly effective technique for identifying promising lead compounds and advancing prospective pharmaceutical medicines addressing a wide range of disorders [13][14][15]. Currently, a variety of computational techniques are being used to identify interesting lead entities from large compound repositories.…”
Section: Introductionmentioning
confidence: 99%